Listening Without Understanding: Central Bank Transparency, Financial Markets and the Crowding Out of Private Information - Clemens J. M. Kool; Stephanie Rosenkranz; M. Middeldorp (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2007)
The trend of monetary policy transparency has recently extended itself to the practice of providing guidance on the likely direction of policy rates. There is a risk that communicating the central bank's own outlook for interest rates actually undermines the financial markets' ability to predict monetary policy. This paper analyzes this risk using the Diamond (1985) model of a financial market, which includes both costly private information acquisition and a costless public signal. We demonstrate that a sufficiently precise signal from the central bank can result in a deterioration of the financial market's ability to predict monetary policy through the crowding out of private information acquisition. Central banks could alleviate this risk with a policy of limiting the guidance offered to the financial market in order to leave sufficient scope for private information acquisition.
Keywords: 330; Interest Rates; Monetary Policy; Information and Financial Market Efficiency; Communication; Transparency; Information Acquisition